Nutrieye: An Android-Based Food Nutritional Value Recognition App Using Yolov8 Algorithm - Aseoche, Nicholai Gian B.; Al-Ismail, Shahed Ibrahim B; Dannug, Edvince Joy M (IC-ITECHS, 2024)
Good nutrition is essential for a healthy lifestyle, yet many people consume calorie-dense, low-nutrition foods, contributing to malnutrition. While food recognition systems exist, few cater specifically to Filipino dietary needs. This study developed NutriEye, an Android-based app that identifies the nutritional content of common Filipino foods and recommends portion sizes based on user profiles and dietary needs. Using the Food Nutrition and Research Institute's (FNRI) Philippine Food Composition Table and Dietary Reference Intake Chart, the app leverages the YOLOv8 algorithm to analyze food images, estimate nutritional values, and calculate suitable servings. The app's accuracy was tested through evaluation metrics and validated using ISO/IEC 25010 standards for quality, including functionality, efficiency, usability, and security. Feedback from 100 respondents confirmed the app’s effectiveness in promoting better nutrition management tailored for Filipino users.